2021
DOI: 10.1186/s12936-021-03917-6
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of RDT, light microscopy, and PET-PCR for detecting Plasmodium falciparum malaria infections in the 2018 Zambia National Malaria Indicator Survey

Abstract: Background Zambia continues to advance on the path to elimination with significant reductions in malaria morbidity and mortality. Crucial components that have contributed to progress thus far and are necessary for achieving the national malaria elimination goals include properly identifying and treating all malaria cases through accurate diagnosis. This study sought to compare and assess the diagnostic performance of Rapid Diagnostic Tests (RDT) and Light Microscopy (LM) with photo-induced elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
(38 reference statements)
0
10
1
Order By: Relevance
“…When this technique was described, the authors suggested using 2 µL of DNA to obtain a detection limit of 3.2 -5.8 parasites/µL [22]. Subsequently, the starting DNA volume has been increased to 5 µL [23,24,[41][42][43][44][45] to improve the sensitivity of the method. In this study, 5 µL of DNA and a cycle threshold (Ct) below 40 were used, as recommended by most reports [21,24,41,42,44], although some authors have used 40.5 or 41 [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…When this technique was described, the authors suggested using 2 µL of DNA to obtain a detection limit of 3.2 -5.8 parasites/µL [22]. Subsequently, the starting DNA volume has been increased to 5 µL [23,24,[41][42][43][44][45] to improve the sensitivity of the method. In this study, 5 µL of DNA and a cycle threshold (Ct) below 40 were used, as recommended by most reports [21,24,41,42,44], although some authors have used 40.5 or 41 [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…For this study, we included 459 PET-PCR positive P. falciparum samples from ten provinces for sequencing ( Figure S2) . The majority of DBS samples collected from three provinces with low malaria transmission (Central, Lusaka and Southern) were negative by PET-PCR as well as by RDT and microscopy 14 limiting the number of samples that could be sequenced from these three provinces. DBS were registered and tracked in a database, where location, date of collection, and other metadata were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…The number of households was used as a measure of size for selecting the primary sampling units (PSU) which were the EAs or clusters. Blood specimens from children younger than 5 years were tested by RDT, microscopy and PET-PCR 14 and an additional dried-blood spot (DBS) was collected for parasite whole-genome sequencing. De-identified DBS were stored individually in plastic bags with silica gel desiccant at −20 °C before being shipped to the Carpi Laboratory at Purdue University, where they were stored at room temperature with fresh silica gel packets.…”
Section: Methodsmentioning
confidence: 99%
“…In Zambia, despite intensified control interventions, P. falciparum malaria remains endemic with highly heterogeneous transmission and variable parasite prevalence at subnational levels, making elimination efforts challenging 12 . Despite a north-to-south transmission intensity gradient based on epidemiological data, the country is using similar control strategies across provinces, such as mass distributions of long-lasting insecticide treated mosquito nets (LLINs), annual indoor residual spraying (IRS), prompt diagnosis with rapid diagnostic tests (RDTs) and light microscopy, and treatment with artemisinin-based combination therapy (ACT) 13 , 14 . Understanding the genomic structure of parasite populations and measuring the degree of parasite genetic relatedness are essential to assess transmission dynamics and the dispersal of infections, and to glean insights into how parasite populations respond to selection pressure exerted by different control interventions 3 , 15 .…”
Section: Introductionmentioning
confidence: 99%